Hubungan Antara Perilaku Hidup Bersih dan Sehat dengan Kejadian Pneumonia pada Balita di Wilayah Kerja Puskesmas Mlati II Yogyakarta - Nining Fitrianingsih; Titih Huriah; Sri Muryati (LPPM STIKES Guna Bangsa, 2014)
Background: The United Nations Children's Fund (UNICEF) and the World Health Organization (WHO) in 2006 stated, pneumonia is the most important child killer. Every year, more than 2 million children die from pneumonia, means that 1 in 5 infants died in the world. Health status is not only determined by health service, but the most dominant are environment and people’s behavior. One efffort to change people’s behavior, in order to support the improvement of health is by implemented of Clean And Healthy Life Behavior Program. Aim: To know the correlation between the behavior of clean and healthy life with incident pneumonia in children in the work area of Mlati II Primary Health Center Yogyakarta. Methods: The reseach method used an analytical survey research with cross sectional survey design. Total population in this study were 2.243 childrens, while the technical sampling is done with cluster techniques obtained as 96 samples of children. Statistical tests used chi square and than analized the relationship using Prevalence Ratio (PR). Results:Result showed p value = 0.000 and PR = 2.88 on the relationship between the incidence of pneumonia with clean and healthy life behavior. Exclusive breastfeeding variables showed p value 0.00 and PR = 3.811. Variabel wash hand shows the results p value 0.034 and PR= 1.277. Variable smoking habits of family members is p value 0.026. and PR = 9.831. Conclusion: There are relation between the behavior of clean and healthy life, exclusive breastfeeding, hand washing with soap and smoking habits of family members with the incidence of pneumonia.